Torsional natural frequency tuning by means of pneumatic flexible shaft couplings - Peter KAŠŠAY; Matej URBANSKÝ (Scientific Journal of Silesian University of Technology. Series Transport, 2015)
This article deals with the use of pneumatic flexible shaft couplings as device for tuning torsional natural frequencies of mechanical systems. These couplings are using air bellows as flexible elements. Their torsional stiffness can be changed by air pressure change, the natural frequencies of whole mechanical system may be adjusted on desired value.